EVALUATION of FAMILY PLANNING METHODS in TERMS of WOMEN’S SEXUAL LIFE - ŞİMŞEK KÜÇÜKKELEPÇE, Didem and KAYA SENOL, Derya and AYDIN ÖZKAN, Semiha (Göbeklitepe Medical Science Journal, 2021)
Aim: This study aims to identify the effects of family planning (FP) methods on women’s sexual life. Methods: This descriptive and cross-sectional study utilized a relational screening design. The sample of the study included 264 women who visited the gynecology clinic for any reason. Data were collected through the Participant Information Form and the Female Sexual Function Index (FSFI). Results: Significant differences were detected in the FSFI sub-scales of Arousal, Lubrication, Orgasm and the FSFI total mean score (p<0,05). Further analyses showed that the Arousal, Lubrication, and Orgasm sub-scales and FSFI total score were highest in women who used COC and lowest in women who did not use FP methods; the statistical difference was found to be between women who used COC and women who did not use FP methods (p<0,05). Conclusion: It was found that the family planning methods used by women did not affect the Desire, Satisfaction, and Pain sub-scales of sexual function, but they affected the Arousal, Lubrication, Orgasm sub-scales and FSFI total mean score.